Canonical hedgehog signalling regulates hepatic stellate cell‐mediated angiogenesis in liver fibrosis. (31st January 2017) - Zhang, Feng; Hao, Meng; Jin, Huanhuan; Yao, Zhen; Lian, Naqi; Wu, Li; Shao, Jiangjuan; Chen, Anping; Zheng, Shizhong
Abstract : BACKGROUND AND PURPOSE: Hepatic stellate cells (HSCs) are liver‐specific pericytes regulating angiogenesis during liver fibrosis. We aimed to elucidate the mechanisms by which hedgehog signalling regulated HSC angiogenic properties and to validate the therapeutic implications. EXPERIMENTAL APPROACH: Rats and mice were treated with carbon tetrachloride for in vivo evaluation of hepatic angiogenesis and fibrotic injury. Diversified molecular approaches including real‐time PCR, Western blot, luciferase reporter assay, chromatin immunoprecipitation, electrophoretic mobility shift assay and co‐immunoprecipitation were used to investigate the underlying mechanisms in vitro . KEY RESULTS: Angiogenesis was concomitant with up‐regulation of Smoothened (SMO) and hypoxia inducible factor‐1α (HIF‐1α) in rat fibrotic liver. The SMO inhibitor cyclopamine and Gli1 inhibitor GANT‐58 reduced expression of VEGF and angiopoietin 1 in HSCs and suppressed HSC tubulogenesis capacity. HIF‐1α inhibitor PX‐478 suppressed HSC angiogenic behaviour, and inhibition of hedgehog decreased HIF‐1α expression. Furthermore, heat shock protein 90 (HSP90) was characterized as a direct target gene of canonical hedgehog signalling in HSCs. HSP90 inhibitor 17‐AAG reduced HSP90 binding to HIF‐1α, down‐regulated HIF‐1α protein abundance and decreased HIF‐1α binding to DNA. 17‐AAG also abolished 1‐stearoyl‐2‐arachidonoyl‐sn‐glycerol (SAG) (a SMO agonist)‐enhanced HSC angiogenic properties. Finally, the natural compound ligustrazine was found to inhibit canonical hedgehog signalling leading to suppressed angiogenic properties of HSCs in vitro and ameliorated liver fibrosis and sinusoidal angiogenesis in mice. CONCLUSION AND IMPLICATIONS: We have provided evidence that the canonical hedgehog pathway controlled HSC‐mediated liver angiogenesis. Selective inhibition of HSC hedgehog signalling could be a promising therapeutic approach for hepatic fibrosis.